Evolutionary algorithms for mobile ad hoc networks - Dorronsoro, Bernabé. (Nature-inspired computing series., 2014)
This comprehensive guide describes how evolutionary algorithms (EA) may be used to identify, model, and optimize day-to-day problems that arise for researchers in optimization and mobile networking. It provides efficient and accurate information on dissemination algorithms, topology management, and mobility models to address challenges in the field. It is an ideal book for researchers and students in the field of mobile networks.